Zoledronic Acid Prevents Bone Resorption Caused by the Combination of Radium-223, Abiraterone Acetate, and Prednisone in an Intratibial Prostate Cancer Mouse Model - Suominen Mari I.; Knuuttila Matias; Sjöholm Birgitta; Wilson Timothy; Alhoniemi Esa; Mumberg Dominik; Käkönen Sanna-Maria; Scholz Arne (MDPI, 2025)
An increased risk of non-pathological fractures in patients with prostate cancer and bone metastases has been associated with combination treatment with radium-223, abiraterone, and prednisone/prednisolone in the absence of bone-protecting agents. Here, we investigated possible mechanisms leading to this outcome using an intratibial LNCaP model mimicking prostate cancer bone metastases. Male NOD.scid mice were inoculated intratibially with LNCaP prostate cancer cells and treated with vehicle, radium-223, abiraterone, prednisone, zoledronic acid, or their combinations for 28 days. Serum TRACP 5b and PSA levels were measured. Bone structure, quality, and formation rate of non-tumor-bearing and tumor-bearing tibiae were analyzed by microCT, 3-point bending assay, and dynamic histomorphometry, respectively. Radium-223 incorporation into bone was also measured. Radium-223/abiraterone/prednisone combination treatment induced a transient increase in bone resorption indicated by elevated TRACP 5b levels, which was inhibited by concurrent treatment with zoledronic acid. Furthermore, radium-223/abiraterone/prednisone combination reduced periosteal and trabecular new bone formation and the number of osteoblasts, but bone structure or biomechanical quality were not affected. The abiraterone/prednisone treatment decreased radium 223 incorporation into tumor-bearing bone, possibly explaining the lack of additional antitumor efficacy. In conclusion, radium-223/abiraterone/prednisone combination increased bone resorption, which may have been one of the mechanisms leading to an increased fracture risk in patients with mCRPC.